Restoration of Anatomic Parameters and Syndesmotic Reduction After Intramedullary Nailing of Distal Fibular Fractures. Issue 4 (December 2022) - Bastías, Gonzalo F.; Bravo, Francisco; Astudillo, Claudia; Giannini, Esteban; Contreras, Martin; Melo, Rodrigo; Muñoz, Gerardo; Pellegrini, Manuel J.; Cuchacovich, Natalio
Background: Intramedullary nailing of the fibula (FN) is a method of fixation that has proven to be useful for treating distal fibular fractures (DFs). FN minimizes soft tissue complications and provides similar stability to plating, with fewer hardware-related symptoms. Nevertheless, FN has been associated with syndesmotic malreduction and the incapacity of restoring length and rotation of the fibula. We aimed to evaluate the fibular position and syndesmotic reduction after fixation with FN compared with the uninjured ankle in the immediate postoperative period. Methods: Prospective cohort study. Patients with DF fractures treated with IN between January 2017 and January 2020 were included. Immediate postoperative bilateral ankle CT was obtained in all cases. Fibular rotation, length, and translation as well as syndesmotic diastasis were measured on both ankles and compared by 3 independent observers. Results: Twenty-eight patients were included (16 women). The mean age was 46 years (range 16-91). Fracture type distribution according to AO/ASIF classification included 19 patients with 44.B (67.9%), 8 patients with 44.C (28.6%), and 1 patient with a 44.A fracture (3.6%). No significant differences were identified considering fibular rotation ( P = .661), syndesmotic diastasis ( P = .147), and fibular length ( P = .115) between the injured and uninjured ankle. Fibular translation had statistical differences ( P = .01) compared with the uninjured ankle. The intraclass correlation coefficient showed an excellent concordance between observers except for fibular translation on the injured ankle. Conclusion: In this cohort, fixation of DF fractures with FN allows restoration of anatomical parameters of the ankle in terms of fibular rotation, length, and syndesmotic diastasis. However, fibular translation had significant differences compared with the uninjured ankle based on bilateral CT scan evaluation. Level of Evidence: Level II, prospective cohort study.